Labour Force Participation and Job Polarization: Evidence from Europe during the Great Recession - Gregory Verdugo; Guillaume Allègre (Institute of Labor Economics (IZA), 2020)
We document how differences in labour demand by gender explain the contrasting evolutions of labour force participation between men and women during the Great Recession in Europe. We first highlight that Europe is characterized by high levels of occupational segregation by gender. As a result, the large job losses in middle-paid occupations during the Great Recession affected male workers disproportionally. In contrast, the fact that higher- and lower-paid occupations were less affected was more favourable to women. Using individual panel data, we investigate how the labour force participation and regional mobility of men and women responded to these shocks. We find that the labour force participation of women increased considerably in the regions most affected by the destruction of men's jobs and with relatively higher labour demand in occupations more likely to employ women. Women with higher levels of education were also more likely to move to regions with higher labour demand in these occupations. We find that not considering the mobility of women with higher education levels can bias the estimates of the impact of labour demand shocks on participation. For men, unemployment increased in response to regional declines in male labour demand. However, regional shocks explain none of the decline in male labour force participation.
Keywords: J21; J23; J24; 330; labor force participation; Great Recession; job polarization